Big Data and Large Scale Methods In Cloud Computing (International Journal of Engineering and Computer Science, 2017)
In this paper I want to highlight what we believe to be the key technology dimensions for evaluating data management solutions. This paper offers and explore define what is meant by big data, We review analytics techniques for text, audio, video, and social media data, We make the case for new statistical techniques for big data, We highlight the expected future developments in big data analytics, Examines cloud data management architectures and Covers Big Data analytics and visualization.It not only considers data management and analytics for vast amounts of unstructured data but also Explores clustering, classification, and link analysis of Big Data.